2011
DOI: 10.4049/jimmunol.1100406
|View full text |Cite
|
Sign up to set email alerts
|

B Cell-Specific Expression of B7-2 Is Required for Follicular Th Cell Function in Response to Vaccinia Virus

Abstract: Follicular Th (TFH) cells are specialized in provision of help to B cells that is essential for promoting protective Ab responses. CD28/B7 (B7-1 and B7-2) interactions are required for germinal center (GC) formation, but it is not clear if they simply support activation of naive CD4 T cells during initiation of responses by dendritic cells or if they directly control TFH cells and/or directly influence follicular B cell differentiation. Using a model of vaccinia virus infection, we show that B7-2 but not B7-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 42 publications
5
62
0
Order By: Relevance
“…Thus, the absence of circulating Tfh cells in patients with two TACI mutations may illustrate dysfunctional GC reactions and decreased isotype-switched antibody secretion. In agreement with this hypothesis, murine models have demonstrated that either CD86 or ICOSL deficiency abolish GC formation and impair the generation of Tfh cells (50)(51)(52). However, expanded Tfh cells driven by overexpression of ICOSL on B cells have been reported in Taci knockout mice (53).…”
Section: Methodsmentioning
confidence: 67%
“…Thus, the absence of circulating Tfh cells in patients with two TACI mutations may illustrate dysfunctional GC reactions and decreased isotype-switched antibody secretion. In agreement with this hypothesis, murine models have demonstrated that either CD86 or ICOSL deficiency abolish GC formation and impair the generation of Tfh cells (50)(51)(52). However, expanded Tfh cells driven by overexpression of ICOSL on B cells have been reported in Taci knockout mice (53).…”
Section: Methodsmentioning
confidence: 67%
“…Indeed, pre-T FH /B cell interactions appear sufficient in early life as adults to initiate T FH cell differentiation (9,35), T cell entry into the follicle, and Bcl6 upregulation (6), but not for GC T FH cell expansion/maintenance. This last stage is known to imply additional requirements, including the SLAM family of receptors and the SLAM-associated proteins required for the formation of sufficiently stable T-B conjugates for T FH cell-GC B cell signaling (27,36,37), sufficient CD80/CD86-CD28 and CD40-CD40L signals to sustain TCR activation (38)(39)(40), and numerous specific GC T FH cell differentiation signals. Neonatal B cells are known for their reduced strength of BCR signaling and lower levels of costimulatory receptors (including CD21, CD40, CD80, and CD86) (3), which could limit their interactions even with functionally competent adoptively transferred adult T FH cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given the sequential interaction of T cells with dendritic cells (DCs) and B cells during humoral responses, this could reflect distinct cell type-specific or kinetic expression patterns between ligands. Of note, studies have documented the importance of either CD86 (52) or CD80 (53) on B cells for T FH generation and GC responses. It is possible that the nature and context of the antigenic challenge dictate the relative requirement for CD80 versus CD86, consistent with the capacity of strong adjuvants to restore the GC response in CD86 −/− mice (65).…”
Section: Discussionmentioning
confidence: 99%
“…The simplest explanation for the capacity of T FR to control GC size is that they limit T FH number and thereby restrict the ability of T cells to rescue GC B cells from death. Because T FH homeostasis is tightly linked to the availability of costimulatory ligands on B cells (52,53), it is easy to envisage how T FR could use the CTLA-4 pathway to control T FH by downregulating costimulatory ligand expression on B cells.…”
Section: Discussionmentioning
confidence: 99%